On-surface synthesis on a bulk insulator surface. (8th March 2018) - Richter, Antje; Floris, Andrea; Bechstein, Ralf; Kantorovich, Lev; Kühnle, Angelika
Abstract: On-surface synthesis has rapidly emerged as a most promising approach to prepare functional molecular structures directly on a support surface. Compared to solution synthesis, performing chemical reactions on a surface offers several exciting new options: due to the absence of a solvent, reactions can be envisioned that are otherwise not feasible due to the insolubility of the reaction product. Perhaps even more important, the confinement to a two-dimensional surface might enable reaction pathways that are not accessible otherwise. Consequently, on-surface synthesis has attracted great attention in the last decade, with an impressive number of classical reactions transferred to a surface as well as new reactions demonstrated that have no classical analogue. So far, the majority of the work has been carried out on conducting surfaces. However, when aiming for electronic decoupling of the resulting structures, e.g. for the use in future molecular electronic devices, non-conducting surfaces are highly desired. Here, we review the current status of on-surface reactions demonstrated on the (10.4) surface of the bulk insulator calcite. Besides thermally induced C–C coupling of halogen-substituted aryls, photochemically induced [2 + 2] cycloaddition has been proven possible on this surface. Moreover, experimental evidence exists for coupling of terminal alkynes as well as diacetylene polymerization. While imaging of the resulting structures with dynamic atomic force microscopy provides a direct means of reaction verification, the detailed reaction pathway often remains unclear. Especially in cases where the presence of metal atoms is known to catalyze the corresponding solution chemistry reaction (e.g. in the case of the Ullmann reaction), disclosing the precise reaction pathway is of importance to understand and generalize on-surface reactivity on a bulk insulator surface. To this end, density-functional theory calculations have proven to provide atomic-scale insights that have greatly contributed to unravelling the details of on-surface synthesis on a bulk insulator surface.